DIETARY CARBOHYDRATE AND PHYSICAL ACTIVITY WITH PREDIABETES WITHIN ADULT WOMEN - khoiriyah, dian; murbawani, etisa ardi; panunggal, binar (Preventif : Jurnal Kesehatan Masyarakat, 2017)
Background & Objective: Prediabetes is a high-risk condition for developing diebetes mellitus. Adultwomen have a higher risk of experiencing prediebetes compared with men. Excessive of simplecarbohydrate intake, low of fiber intake and physical activity risk to increasing blood glucose levels. Thisstudy aimed to analyze the correlation between total carbohydrate intake, simple carbohydrate intake, fiberintake and physical activity with prediabetes in adult women. Materials and Methods: This study used acase control with 36 women aged 45-55 years old in each group chosen by simple random sampling. Foodintake was assessed using by Semi FFQ. Waist circumference was measured using by a tape measure, andphysical activity was obtained using by Long IPAQ. Data were analyzed using by Chi Square, Fisher Exactand multiple logistic regression test. Results: There is a difference in mean of waist circumference, fastingblood glucose, simple carbohydrate intake, fiber intake and physical activity in both groups. The variable atrisk for prediabetes were simple carbohydrate intake (OR=3,94;95%CI 1,23-12,56), fiber intake(OR=2,63;95%CI 0,91-7,63) and fat intake (OR=2,14;95%CI 0,78-5,84). Intake of simple carbohydrate andfiber are the most dominant variable that affecting the incidence of prediabetes with a proportion of 14,5%.There were no correlation between total carbohydrate intake, fiber intake and physical activity withprediabetes in adult women. Conclusion: Excessive simple carbohydrate intake and low fiber intake wererisk in the occurrence of prediabetes.